The purpose and impact of postgraduate knowledge. (14th October 2019) - Wisker, Gina; Robinson, Gillian Diana; Leibowitz, Brenda
Abstract : Purpose: Much research into outcomes of doctoral learning focuses on employability, or the dearth of academic employment in relation to doctoral graduate expectations, emphasising precarity of academic future work. This new work begins with and moves beyond employment issues, highlighting professional practice and personal knowledge development and impact. Design/methodology/approach: Much doctoral education research focuses on the academic identities of postgraduates, their change and alignment to the work and experience of being a doctoral student and beyond, in academic or other jobs. This longitudinal work explores professional and social impact from doctoral research and transformational changes experienced and reported by graduates in two projects. Based on narrative interviewing turned into case studies, it asks fundamental questions about the purpose and impact of postgraduate knowledge. Findings: Respondents emphasised change in their sense of personal, academic and professional identity; immediate impact on professional practice leading to job change, status, changes in practices and longer-term impacts of further influences on professional practice, some international in reach. Research limitations/implications: This small-scale study has widespread implications for understanding the impact of postgraduate knowledge on professional practice and personal development. Practical implications: The work could influence doctoral student intentions and the focus of doctoral programmes. Social implications: Postgraduate knowledge is seen as crucial in theorised and practical contributions to social development. Originality/value: This longitudinal work generates new knowledge, answering questions: What is the purpose of postgraduate knowledge? Who benefits from results? What is the impact from the research? How are outcomes put into professional practice? It found significant developments in professional practice and personal development.